The effect of vacuum packaging on fish balls prepared from Capoeta trutta with different concentrations of liquid smoke - Ozpolat, Emine (Soc Brasileira Ciencia Tecnologia Alimentos, 2022)
In this study, both the evaluation of fish as a different product and he use of liquid smoke in fish balls and the effect of vacuum packaging were investigated. awn and cheap Capoeta trutta were used. Fish balls prepared by adding 3 different rates of liquid smoke (volume/weight) (0%, 0.2% and 0.4% added liquid smoke) were packaged both vacuum and air packaged and stored under 4 +/- 1 degrees C. The samples were analyzed sensory (taste, odor and texturing), chemical (total volatile basic nitrogen-TVB-N, Thiobarbituric acid-TBA,) and microbiological quality (Total mesophilic aerobic bacteria, Coliforms, Escherichia coli, Staphylococcus aureus, yeasts and molds) of storage at 0, 7, 14, 21, 28 and 35 days of storage. When the results were evaluated, it was determined that the addition of liquid smoke positively affected the sensory taste, but it was found that it did not have a significant effect on microbiological and chemical quality. Defineds limits for mesophilic aerobic bacteria and TVB-N were reached vacuum-packaged groups (A, C and E) 35 days, non-vacuum packaged groups (B, D and E) 14 days. It was determined that vacuum packaging extended the shelf life of the product by two weeks on average.
Keywords: fish ball; smoke; liquid smoke; shelf-life; vacuum packaged